The Guideline for Applying Buddhist Principle for Life Development of the Elderly in Nongdon Sub-District, Lamplaimas District, Buriram Province - Ṭhitaguno, Phra Athikarn Wirat; Suvaco, Phramaha Phocana; Arnando, Phramaha Thanorm (Academic MCU Buriram Journal, 2025)
The purposes of this research were: 1) to study life of the elderly in Nongdon sub-district, Lam Plai Mat District, Buriram Province, 2) to study the Buddhist principles used in improving life of the elderly in Nongdon sub-district, Lam Plai Mat District, Buriram Province, and 3) Study the apply Buddhist principles for life development of the elderly in Nongdon sub-district, Lam Plai Mat District, Buriram Province. This is a qualitative field study, involving an analysis of the Tripitaka, relevant documents, and research studies. Structured interviews were conducted and the research results were presented using a descriptive and analytical method. The result of research found that: 1. Condition on health issues of the elderly in Nongdon sub-district, Lam Plai Mat district, Buriram province found that the health issues faced by the elderly in this area reveal several concerns: Physical health issues: most elderly individuals suffer from chronic illnesses, difficulty walking, lack of strength to maintain balance, poor eyesight, and occasional dizziness. These health problems hinder their ability to travel or perform daily activities. Mental health issues: many elderly individuals experience anxiety, stress, and difficulty adjusting to changes. They often feel fearful due to a lack of self-confidence. Social health issues: most elderly individuals live in poverty, with their main source of income coming from government welfare. They are unable to earn additional income, and they face daily expenses, making it difficult to donate to temples or contribute to social welfare activities. 2. Buddhist principles used in improve the life of the elderly in Nongdon sub-district, Lam Plai Mat District, Buriram Province found that 1) Trifold bass of meritorious actions (puññakiriyā-vatthu) are the key principles for good deeds: 1.1) dāna is the act of giving to others or making sacrifices. 1.2) sīla is the practice of moral discipline and self-restraint. 1.3) bhāvanā is the cultivation of meditation and mindfulness to understand the true nature of reality. 2) The Three Characteristics of Existence (Tilakhaṇa): 2.1) aniccā means everything is subject to change and does not last. 2.2) dukkha means life involves suffering or dissatisfaction, and nothing is permanent. 2.3) anattā means there is no permanent, unchanging self or soul. 3) The Four Bases of Practice (bhāvanā): 3.1) kāyā-bhāvanā means the development of the body, including physical discipline. 3.2) sīla- bhāvanā means the cultivation of virtue and ethical behavior. 3.3) cittā-bhāvanā means the development of the mind through meditation. 3.4) paññā-bhāvanā means the cultivation of wisdom and insight into the nature of reality. These Buddhist teachings help the elderly individuals understand the processes of physical and mental change, as well as the social environment around them. They also encourage the elderly to understand the nature of life and society. 3. An application of Buddhist principles to Improve the life of the elderly in Nongdon sub-district, Lam Plai Mat District, Buriram Province found that the elderly is able to understand the Threefold meritorious principles (dāna, sīla, and bhāvanā) as core teachings of Buddhism. These principles guide them towards a deeper understanding of Buddhist teachings. However, practicing these principles is challenging, as many elderly individuals are preoccupied with family responsibilities and face various difficulties in their daily lives. Apply the principle of the three characteristics of change, hardship, and non-self to life appropriately in terms of physical, mental, and social aspects. The Four Bases of Practice; kaya-bhāvanā, sīla-bhāvanā, citta-bhāvanā, and paññā-bhāvanā are practiced to some extent, with some being more consistent than others. Moral practices such as keeping the precepts are done regularly, but mental and wisdom development require continuous practice and a detailed application of wisdom. The elderly believes that if they follow these teachings correctly, they can lead a happy life, and society can coexist harmoniously.